Report: Proposed interior design scheme of Canon Showroom for Canon Malaysia Sdn Bhd at No. 1, Jalan Sultan Azlan Shah, 31400 Ipoh, Perak Darul Ridzuan / Muhammad Asyraf Yahya - Yahya, Muhammad Asyraf (Faculty of Architecture, Planning and Surveying, 2011)
Final student in Diploma Architecture needs to come out with project report in order to understand the whole final project in every aspects started from basic level to final presentation. The final project is Proposed New Interior Design Scheme of Canon Showroom for Canon Malaysia Incorporated at No. 1, Jalan Sultan Azlan Shah, 31400 Ipoh, Perak Darul Ridzuan. As every Malaysian people know, Canon Incorporated is one of a gigantic company on its field. Its well-known through-out the globe. Their successful business by variety of business inspiring people and young entrepreneur to jump start their carrier on Business world. Therefore, by proposing a showroom for Canon that specialized in camera, people can affiliate their free time to visit on Canon Showroom. Apart of giving out an info to people, they also could buy camera that catch their eyes during the displayed inside the showroom. By planning a Canon Showroom at Ipoh, photographer could spend their times on their hobby that is real life camera display.